Do White Women Support Black Women who Confront Sexism Versus Racism? - Keller, Benjamin B. (Tufts Archival Research Center, 2021)
Previous research has demonstrated that confronting discrimination can be beneficial for overall reduction of prejudice, but comes with significant costs. Those who confront discrimination may be viewed as troublemakers and less likeable than those who do not confront it. Previous literature on perceptions of discrimination confrontation have largely studied perceptions toward individuals who confront discrimination to a single identity (e.g. gender or race), and the perceptions of those who may not share similar experiences of discrimination with the claimant. The present study aims to address this gap in literature by examining White women and men’s perceptions of a Black woman who confronted discrimination. Participants recruited through Tufts University SONA database of studies (N = 212) were White women and men asked read a scenario where a Black woman confronted discrimination, manipulated to be either racism or sexism. Participants rated their attitudes toward the Black woman as a troublemaker, and as likeable. We hypothesized that White women, compared to men, would be more sympathetic to a Black woman who confronted sexism than racism, due to the fact that a White woman may be able to envision herself as a victim of sexism. Results did not support the hypothesis, and found no meaningful difference across gender or confrontation conditions in participant responses. Contradicting previous literature, results indicated that participants did not view the Black woman as unlikeable or a troublemaker across conditions.; Advisor: Dr. Jessica Remedios